A 4‐day‐old newborn with an isolated sternal cleft: A rare case and literature review. Issue 12 (12th October 2021) - Xu, Shoujun; Yang, Chunlan; Gan, Yungen; Jiang, Guihua
Summary: An isolated sternal cleft is an orphan congenital defect of the sternum that presents from birth to adulthood. We report the case of a 4‐day‐old newborn with an isolated congenital cleft sternum. We also reviewed the related literature and operative options.